If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4x + 2)(6 + -3x) = 0 Reorder the terms: (2 + 4x)(6 + -3x) = 0 Multiply (2 + 4x) * (6 + -3x) (2(6 + -3x) + 4x * (6 + -3x)) = 0 ((6 * 2 + -3x * 2) + 4x * (6 + -3x)) = 0 ((12 + -6x) + 4x * (6 + -3x)) = 0 (12 + -6x + (6 * 4x + -3x * 4x)) = 0 (12 + -6x + (24x + -12x2)) = 0 Combine like terms: -6x + 24x = 18x (12 + 18x + -12x2) = 0 Solving 12 + 18x + -12x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '6'. 6(2 + 3x + -2x2) = 0 Factor a trinomial. 6((2 + -1x)(1 + 2x)) = 0 Ignore the factor 6.Subproblem 1
Set the factor '(2 + -1x)' equal to zero and attempt to solve: Simplifying 2 + -1x = 0 Solving 2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 0 + -2 -1x = 0 + -2 Combine like terms: 0 + -2 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2Subproblem 2
Set the factor '(1 + 2x)' equal to zero and attempt to solve: Simplifying 1 + 2x = 0 Solving 1 + 2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 2x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 2x = 0 + -1 2x = 0 + -1 Combine like terms: 0 + -1 = -1 2x = -1 Divide each side by '2'. x = -0.5 Simplifying x = -0.5Solution
x = {2, -0.5}
| 400=x^2+42x | | 0=18x^2+90x-432 | | z6y4/z6y5 | | X^2-10x+20=8 | | a/6=7=11 | | -4s+30= | | -6z+12=24 | | -14-5n=2(5n+7)+5n | | (2x+3y)dx+(y+2)dy=0 | | -4s+15=25 | | (4x+2)+(5x-7)+3x=180 | | (2x-1)(5x^2+6x-3)= | | y^3+y=50 | | tanx=1.274 | | 187x=374 | | (2w^2-3w+1)(4w^2-7w-2)= | | 12=x+9-5x | | X+(-11)=13 | | x^2+y^2=1 | | (7x^2-5x-3)(2x+4)= | | X-(-9)=24 | | +2n=+4 | | 1/64 | | ln(3x-15)=5 | | y=x2+2 | | (3v-4)(2v^2+6v+7)= | | 5x-9=6(x+3) | | 3x+750+12x=200 | | F(x)=e^8x | | (5u^2+u-6)(u^2+3u-2)= | | 2^5x=3/2^7 | | 0,6427=x/7.5 |